Dietary nitrate does not enhance running performance in elite cross-country skiers - Peacock, O.; Tjønna, A. E.; James, P.; Wisløff, U.; Welde, B.; Böhlke, N.; Smith, A.; Stokes, K.; Cook, C.; Sandbakk, O. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The objective of this study is to examine the effects of acute ingestion of dietary nitrate on endurance running performance in highly trained cross-country skiers. Dietary nitrate has been shown to reduce the oxygen cost of submaximal exercise and improve tolerance of high-intensity exercise, but it is not known if this holds true for highly trained endurance athletes.